1993
DOI: 10.1111/j.1748-1716.1993.tb09558.x
|View full text |Cite
|
Sign up to set email alerts
|

In‐vivo effects of endothelin‐1 and ETa receptor blockade on arterial, venous and capillary functions in skeletal muscle

Abstract: Results from in vitro studies have indicated that endothelin-1 is a main candidate for endothelium-derived contracting factors. The aim of this in vivo study was to describe in quantitative terms the effects of endothelin-1 (ET-1), and of ETA receptor blockade, on vascular tone (resistance) in large-bore arterial resistance vessels (> 25 microns), small arterioles (< 25 microns) and the veins, as well as on capillary pressure and fluid exchange in cat gastrocnemius muscle. Endothelin-1 (100-1600 ng kg-1 min-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
(14 reference statements)
3
22
0
Order By: Relevance
“…The present result, demonstrating that ETBreceptor stimulation leads to a constrictor response, could a priori suggest that the vasoconstrictor response to ET-1 can be mediated by both receptor subtypes in skeletal muscle in vivo. However, we have previously demonstrated that the ET-1-mediated vasoconstriction in muscle in vivo can be abolished by selective ETA-receptor blockade alone (FR 139317;Ekelund et al, 1993). Further, in the present in vitro study, FR139317 competitively inhibited the ET-l-induced contraction of the femoral artery and vein.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…The present result, demonstrating that ETBreceptor stimulation leads to a constrictor response, could a priori suggest that the vasoconstrictor response to ET-1 can be mediated by both receptor subtypes in skeletal muscle in vivo. However, we have previously demonstrated that the ET-1-mediated vasoconstriction in muscle in vivo can be abolished by selective ETA-receptor blockade alone (FR 139317;Ekelund et al, 1993). Further, in the present in vitro study, FR139317 competitively inhibited the ET-l-induced contraction of the femoral artery and vein.…”
Section: Discussionsupporting
confidence: 49%
“…The initial transient vasodilator responses to IRL 1620 and BQ 3020 were not significantly different from those elicited by the endothelins (Ekelund et al, 1993;Ekelund, 1994) with regard to amplitude, duration and time to peak dilatation. This finding seems to support our previous tentative conclusion (Ekelund, 1994) that the dilator responses to the endothelins are mediated via the ETB-receptor.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations